I ♥ cheese : a cookbook : 60 ooey, gooey, delicious meals for serious cheese lovers - Metaxa-albu, Mihaela (Page Street Publishing Co., 2020)
Celebrating the world's most beloved culinary ingredient, this inspired collection of delicious recipes helps readers discover new and exciting ways to enjoy cheese through creative recipes that highlight cheese in unique meals.